# FA to Regular Expressions construction

This topic designed for finite automata FA to regular expression (RE) construction.

**Case 1:**

**Finite Automata for RE = 0**

For a regular expression (RE) ‘0’, we can construct the following FA −.

**Case 2:**

**Finite Automata for RE = 01**

For a RE ‘01’, we can construct the following FA −.

**Case 3:**

**Finite Automata for RE = (0+1)**

For a RE ‘(0+1)’, we can construct the following −.

**Case 4:**

**Finite Automata for RE = (0+1)***

For a RE ‘(0+1)*’, we can construct the following –.

**Case 5:**

**Finite Automata for RE = 0(0+1)*1**

This expression can also be known as starting from ‘0’ and ending on ‘1’.

**Case 6:**

**Finite Automata for RE = 1(0+1)*0**

This expression can also be known as starting from ‘1’ and ending on ‘0’.

**Case 7:**

**Finite Automata for RE = 1(0+1)*0 + 0(0+1)*1**

This expression can also be known as starting and ending on different points.

**Case 8:**

**Finite Automata for RE = (0+1)*11(0+1)***

This expression can also be known as a string containing double ‘11’.

**Case 9:**

**Finite Automata for “Exactly one 0 and two 11”.**